2012
DOI: 10.1155/2012/467059
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Endothelium in HPS Pathogenesis and Potential Therapeutic Approaches

Abstract: American hantaviruses cause a highly lethal acute pulmonary edema termed hantavirus pulmonary syndrome (HPS). Hantaviruses nonlytically infect endothelial cells and cause dramatic changes in barrier functions of the endothelium without disrupting the endothelium. Instead hantaviruses cause changes in the function of infected endothelial cells that normally regulate fluid barrier functions of capillaries. The endothelium of arteries, veins, and lymphatic vessels is unique and central to the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 186 publications
(396 reference statements)
1
35
0
Order By: Relevance
“…Hypoxia and ANDV infection enhance the formation of giant MECs and LECs. The ability of ANDV infection to cause the formation of giant LECs in response to VEGF was previously reported and suggested to be regulated by rapamycin-sensitive mTOR signaling responses (41). Combined with the results presented above, these findings suggested that hypoxic conditions might be sufficient to increase the size of ANDV-infected MECs and LECs.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Hypoxia and ANDV infection enhance the formation of giant MECs and LECs. The ability of ANDV infection to cause the formation of giant LECs in response to VEGF was previously reported and suggested to be regulated by rapamycin-sensitive mTOR signaling responses (41). Combined with the results presented above, these findings suggested that hypoxic conditions might be sufficient to increase the size of ANDV-infected MECs and LECs.…”
Section: Resultssupporting
confidence: 73%
“…Consistent with hantavirus inactivation of ␣ v ␤ 3 , the knocking out of ␤ 3 or inhibition of ␣ v ␤ 3 promotes VEGFR2-directed endothelial cell permeability (56)(57)(58)(59)(60). A recent report further demonstrated that ANDV infects lymphatic endothelial cells (LECs) and both enhances LEC permeability and causes the formation of giant LECs in response to VEGF (41,47). These findings indicate that both microvascular leakage and pulmonary fluid clearance by lymphatic vessels are likely to be altered by ANDV infection of MECs and LECs.…”
mentioning
confidence: 77%
See 3 more Smart Citations